Analisis Perbandingan Finite State Automata (FSA) Dengan Breadth First Search (BFS) Terhadap Desain Sistem Aplikasi Screening Awal Karyawan - Ahmad Ramadhan; Maria Yustina Tuga; Siti Aisyah Sri Rahayu N; Rismayani Rismayani (UNIVERSITAS INDO GLOBAL MANDIRI, 2023)
This study aims to achieve a business process needed by a company in implementing the company's vision and mission. Therefore, a selection process is needed to be used by the company as a criterion to meet company standards. So this research is based on the implementation of the initial screening of too many employees so that HRD work is hampered. Thus, this application is built using the BFS method. We tried to analyze the implementation of the employee recruitment screening algorithm by comparing the BFS and FSA methods. In addition to building an application using the BFS method, the author also built it using the FSA method to see which of these two methods is more accurate to use in the initial employee screening selection. So the method we are currently using is the Breadth-First Search (BFS) method because it can describe the process starting from the initial selection of employees by explaining the registration steps to the final process, namely decisions from predetermined screening results. So the expected result is creating an application to help HRD as an initial selection of employee recruitment. The results obtained in this study are between the Breadth-First Search Algorithm (BFS) and the Finite State Automata (FSA) method. Employee start.Keywords : Screening, Employee, Recruitment, FSA (Finite State Automata)